MATHEMATICAL THINKING ABILITY: A LITERATURE REVIEW ON COGNITIVE STYLES AND THE PROBLEM-BASED LEARNING MODEL - Riwanda, Mesa; Nindiasari, Hepsi; Anriani, Nurul; Fatah, Abdul (Jurnal Pendidikan Matematika dan IPA, 2026)
This study explores the relationship between mathematical creative thinking, students’ cognitive styles (Field Independent and Field Dependent), and the Problem Based Learning (PBL) model in solving open-ended problems. Using a Systematic Literature Review (SLR) based on the PRISMA framework, this research analyzed 15 relevant articles published between 2018 and 2025. The findings reveal that cognitive styles influence students' creative thinking patterns. Field Independent students tend to produce more original and flexible solutions, while Field Dependent students perform better with structured guidance. Moreover, PBL is effective in enhancing the dimensions of creative thinking—fluency, flexibility, originality, and elaboration—especially when combined with open-ended tasks. This review highlights the importance of adaptive instructional design that integrates PBL and accounts for students’ cognitive styles to foster mathematical creative thinking skills.